Duration Judgments Over Multiple Elements - Ayhan, Inci; Revina, Yulia; Bruno, Aurelio; Johnston, Alan (Frontiers in Psychology, 2012)
We investigated the limits of the number of events observers can simultaneously time. For single targets occurring in one of eight positions sensitivity to duration was improved for spatially pre-cued items as compared to post-cued items indicating that exogenous driven attention can improve duration discrimination. Sensitivity to duration for pre-cued items was also marginally better for single items as compared to eight items indicating that even after the allocation of focal attention, distracter items can interfere with the encoding of duration. For an eight item array discrimination was worse for post-cued locations as compared to pre-cued locations indicating both that attention can improve duration discrimination performance and that it was not possible to access a perfect memory trace of the duration of eight elements. The interference from the distracters in the pre-cued eight item array may reflect some mandatory averaging of target and distracter events. To further explore duration averaging we asked subjects to explicitly compare average durations of multiple item arrays against a single item standard duration. Duration discrimination thresholds were significantly lower for single elements as compared to multiple elements, showing that averaging, either automatically or intentionally, impairs duration discrimination. There was no set size effect. Performance was the same for averages of two and eight items, but performance with even an average of two items was worse than for one item. This was also true for sequential presentation indicating poor performance was not due to limits on the division of attention across items. Rather performance appears to be limited by an inability to remember or aggregate duration information from two or more items. Although it is possible to manipulate perceived duration locally, there appears to be no perceptual mechanisms for aggregating local durations across space.